English Teachers' Perspectives on ChatGPT as a Writing Assistant in Narrative Writing: Benefits and Challenges for EFL Instruction - Muchlisin Yahya Yanuarsyah; Zainul Aminin (Al-Qalam Institue, 2026)
Writing is an essential skill in English as a Foreign Language (EFL) learning, particularly in developing students’ ability to produce narrative texts. This study aims to explore English teachers’ perspectives on the use of ChatGPT as a writing assistant in narrative writing instruction and to identify its perceived benefits and challenges. A qualitative study employing a basic interpretative design was conducted with five English teachers selected through purposive sampling based on their experience using ChatGPT in teaching. Data were collected through open-ended questionnaires and semi-structured interviews and analyzed using thematic analysis. The findings indicate that teachers perceive ChatGPT as a valuable tool for supporting students’ idea generation, language development, and understanding of narrative text structure. It also assists teachers in preparing instructional materials and facilitating classroom activities. However, teachers also reported challenges, including students’ over-reliance on ChatGPT, ethical concerns related to plagiarism, difficulties in monitoring responsible use, and the potential reduction of students’ critical thinking skills. These findings imply that ChatGPT can effectively support narrative writing instruction when integrated with appropriate pedagogical guidance, ethical awareness, and teacher supervision to promote meaningful and responsible learning.